2017
DOI: 10.1038/s41598-017-15074-5
|View full text |Cite
|
Sign up to set email alerts
|

N-Myc-Interacting Protein Negatively Regulates TNF-α-Induced NF-κB Transcriptional Activity by Sequestering NF-κB/p65 in the Cytoplasm

Abstract: NF-κB is a major regulator of gene transcription involved in immune, inflammation, apoptosis and stress responses. However, the regulation of NF-κB is not completely understood. Here, we report that the N-Myc and STATs Interactor (NMI), an IFN-inducible protein, is an important negative regulator of NF-κB activity. We found that NMI negatively regulates TNF-α-induced IL-6 and IL-1β production in HeLa cells. Overexpression of NMI inhibits NF-κB transcriptional activity, in contrast, depletion of NMI by shRNA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Furthermore, intracellular NMI inhibits immune response to reduce inflammatory cytokines in cancer. 25 Therefore, our observation showed that NMI in PBMCs from HBV-ACLF was increased, suggesting that NMI could also serve as an intracellular immune regulator in the development of HBV-ACLF in addition to act as a circulating inflammatory mediator. We acknowledge that there is certain discrepancy of NMI between serum and PBMCs from HCs and CHB.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, intracellular NMI inhibits immune response to reduce inflammatory cytokines in cancer. 25 Therefore, our observation showed that NMI in PBMCs from HBV-ACLF was increased, suggesting that NMI could also serve as an intracellular immune regulator in the development of HBV-ACLF in addition to act as a circulating inflammatory mediator. We acknowledge that there is certain discrepancy of NMI between serum and PBMCs from HCs and CHB.…”
Section: Discussionmentioning
confidence: 60%
“…Our study also showed that NMI was significantly increased in PBMCs from HBV‐ACLF patients, suggesting that upregulated NMI in PBMCs may be related to excessive inflammation response in the development of HBV‐ACLF. Furthermore, intracellular NMI inhibits immune response to reduce inflammatory cytokines in cancer . Therefore, our observation showed that NMI in PBMCs from HBV‐ACLF was increased, suggesting that NMI could also serve as an intracellular immune regulator in the development of HBV‐ACLF in addition to act as a circulating inflammatory mediator.…”
Section: Discussionmentioning
confidence: 69%
“…The NF-κB signaling pathway is closely related to cell proliferation and oncogenesis. In response to numerous stimuli including tumor necrosis factor alpha (TNF-α) and bacterial lipopolysaccharide (LPS), NF-κB is activated and translocated into the nucleus from the cytoplasm, where it acts as a transcription factor to regulate its downstream target genes [35,36,[41][42][43]. In our study, miR-139-5p and PMP22 knockdown both suppress the NF-κB signaling pathway, and PMP22 overexpression rescued the miR-139-5p-induced NF-κB reporter activity, suggesting that PMP22 may enhance tumor proliferation through the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB pathway promotes cell proliferation and oncogenesis by protecting cells from apoptosis [35,36]. We speculated that miR-139-5p might regulate PMP22 through the NF-κB pathway.…”
Section: Mir-139-5p Represses Pmp22 By Inhibiting the Nf-κb Pathwaymentioning
confidence: 99%
“…And then, NF-κB is transferred to the nucleus to promote NF-κB-dependent gene transcription. NF-κB mainly regulates the transcriptional effects of IL-6, IL-1β, VCAM-1, COX-2, TNF-α, and JUN [64][65][66][67], thereby mediating the expression of proinflammatory factors to enhance inflammation.…”
Section: Functional Analysis and Pathways Of T2dmmentioning
confidence: 99%